Luminous Infrared Sources in the Local Group: Identifying the Missing Links in Massive Star Evolution. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Britavskiy, N.; Bonanos, A. Z.; Mehner, A.
Abstract: We present the first systematic survey of dusty massive stars (RSGs, LBVs, sgB[e]) in nearby galaxies, with the goal of understanding their importance in massive star evolution. Using the fact that these stars are bright in mid-infrared colors due to dust, we provide a technique for selecting and identifying dusty evolved stars based on the results of Bonanos et al. (2009, 2010 ), Britavskiy et al. (2014 ), and archival Spitzer /IRAC photometry. We present the results of our spectroscopic follow-up of luminous infrared sources in the Local Group dwarf irregular galaxies: Pegasus, Phoenix, Sextans A and WLM. The survey aims to complete the census of dusty massive stars in the Local Group.